Hybrid Cognitive‐Behavioral Therapy Intervention for Adolescents With Co‐Occurring Migraine and Insomnia: A Single‐Arm Pilot Trial. Issue 7 (27th August 2018) - Law, Emily F.; Wan Tham, See; Aaron, Rachel V.; Dudeney, Joanne; Palermo, Tonya M.
Abstract : Objective: This study aimed to evaluate feasibility and acceptability of a hybrid cognitive‐behavioral therapy intervention for adolescents with co‐occurring migraine and insomnia. Background: Many youth with chronic migraine have co‐occurring insomnia. Little research has been conducted to evaluate behavioral treatments for insomnia in youth with migraine. Design and Methods: We conducted a single‐arm pilot trial to evaluate the feasibility and acceptability of delivering cognitive‐behavioral therapy for insomnia to 21 youth (mean age 15.5, standard deviation 1.6) with co‐occurring chronic migraine and insomnia. Adolescents completed up to 6 individual treatment sessions over 6 to 12 weeks, and 1 booster session 1 month later. Assessments included a prospective 7‐day headache and sleep diary, and self‐report measures of insomnia, sleep quality, sleep habits, and activity limitations at pre‐treatment, immediate post‐treatment, and 3‐month follow‐up. Results: Adolescents demonstrated good treatment adherence and families rated the intervention as highly acceptable. Preliminary analyses indicated improvements from pre‐treatment to post‐treatment in primary outcomes of headache days ( M  = 4.7, SD   = 2.1 vs M  = 2.8, SD = 2.7) and insomnia symptoms ( M  = 16.9, SD = 5.2 vs M  = 9.5, SD = 6.2), which were maintained at 3‐month follow‐up ( M  = 2.7, SD = 2.8; M  = 9.3, SD = 5.0, respectively). We also found improvements in secondary outcomes of pain‐related activity limitations as well as sleep quality, sleep hygiene, and sleep patterns. Conclusions: These preliminary data indicate that hybrid cognitive‐behavioral therapy is feasible and acceptable for youth with co‐occurring chronic migraine and insomnia. Future randomized controlled trials are needed to test treatment efficacy on migraine, sleep, and functional outcomes. ClinicalTrials.gov Identifier: NCT03137147.